The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1007/s00464-015-4495-0
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic radical cholecystectomy for suspected early gall bladder carcinoma: thinking beyond convention

Abstract: Laparoscopic radical cholecystectomy with lymphadenectomy can be a viable alternative for management of early GBC in terms of technical feasibility and oncological clearance along with offering the conventional advantages of minimal access approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 36 publications
0
38
0
Order By: Relevance
“…Tumor recurrence occurred in a few patients, with systemic recurrence being more frequent incidence of systemic recurrence. The survival outcomes after laparoscopic surgery were similar to or better than those after open surgery [11-13]. Yoon et al [13] reported favorable long-term outcomes after laparoscopic surgery for GBC, with a 5-year actual survival rate of more than 90%.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Tumor recurrence occurred in a few patients, with systemic recurrence being more frequent incidence of systemic recurrence. The survival outcomes after laparoscopic surgery were similar to or better than those after open surgery [11-13]. Yoon et al [13] reported favorable long-term outcomes after laparoscopic surgery for GBC, with a 5-year actual survival rate of more than 90%.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…The survey and previous reports of laparoscopic extended cholecystectomy for GBC revealed that the most common procedure was liver wedge resection and LN dissection including the LNs around the hepatoduodenal ligament, the common hepatic artery, and the superior portion of the pancreas. With the accumulation of experience, some experts reported more advanced laparoscopic surgeries such as IVb + V segmentectomy, bile duct resection, and para-aortic LN sampling, although the advantages of these procedures remain controversial, even in open surgery [6, 11, 14, 15]. Laparoscopic bile duct resection was performed when the tumor involved the bile duct, but not for complete LN dissection.…”
Section: Discussion and Literature Reviewmentioning
confidence: 99%
“…No significant difference in survival rate between the 2 procedures has been reported. Recent reports on laparoscopic extended cholecystectomy for GBC have demonstrated the technical feasibility and safety of laparoscopic wedge resection, and the feasibility of laparoscopic IVb/V resection for GBC has also been reported [5, 9, 25]. …”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic bile duct resection may be performed in cases with positive cystic duct margins or involvement of the bile duct by tumor. Laparoscopic IVb/V segmentectomy has been performed in some centers [5, 9, 25]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation